rocedwrp

## Answered question

2021-03-08

Find the roots of the function
$f\left(x\right)=\left(2x-1\right)\cdot \left({x}^{2}+2x-3\right)$, with $x\in R$

### Answer & Explanation

StrycharzT

Skilled2021-03-09Added 102 answers

First find the factors of $\left({x}^{2}+2x-3\right).$
Compare the $a{x}^{2}+bx+c$ and ${x}^{2}+2x-3$, implies that $a=1,b=2$, and $c=-3$.
The ac-method of factoring quadratics: To find factors of quadratic $a{x}^{2}+bx+c$, Find two numbers whose sum is b and product is $a\cdot c$.
Here $a\cdot c=1\cdot \left(-3\right)=-3$and $b=2$.
To find factors of quadratic ${x}^{2}+2x-3$, find two numbers whose sum is 2 and the product is -3.
Such numbers are 3 and -1.
The factors of $\left({x}^{2}+2x-3\right)$ are $\left(x+3\right)\left(x-1\right).$
The given function $f\left(x\right)=\left(2x-1\right)\cdot \left({x}^{2}+2x-3\right)$ becomes
$f\left(x\right)=\left(2x-1\right)·\left(x+3\right)·\left(x-1\right)$
Set $f\left(x\right)=0$, implies that
$\left(2x-1\right)\cdot \left(x+3\right)\cdot \left(x-1\right)=0$
By using zero product property,
$\left(2x-1\right)=0,\left(x+3\right)=0,\left(x-1\right)=0$
Implies that,
$2x=1,x=-3,x=1$
That is, the roots of the given function are,
$x=\frac{1}{2},x=-3,x=1.$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?